Implementasi Strategi Pemasaran Menggunakan Analisis STP pada Usaha La.First Bouquet - Mukhamad Samsul; Hilda Shinta Ramadani; Tri Indayani; Lingga Octaviana; Emmywati Emmywati (PUTRA JAWA PUBLISHER, 2023)
Marketing strategy is a means or way to achieve goals in order to get the profit and goals expected by the company. La.first Bouquet is a souvenir business engaged in gift-making services in the form of bouquets of flowers, bouquets of money, bouquets of snacks, and bouquets of headscarves. This study aims to find out how big or how influential the marketing strategy is based on STP analysis (segmenting, targeting, positioning) so that it can compete with competitors healthily and lastingly. The research method used is a qualitative descriptive method, because it directly describes the efforts of La.first Bouquet.